Long-term efficacy of CDK4/6 inhibitors in early HR+, HER2- high-risk breast cancer: An updated systematic review and meta-analysis - Liu, Ying; Su, Jun; Wu, Ping; Lv, Wenjie (Frontiers in Pharmacology, 2025)
BackgroundThe confirmed efficacy of combining CDK4/6 inhibitors with endocrine therapy (ET) in HR+, HER2− early breast cancer patients in longer follow-up necessitates further investigation. This meta-analysis aims to comprehensively assess the impact of follow-up duration on the therapeutic activity in high-risk patients.MethodsWe systematically searched PubMed, Cochrane Library, Embase, Medline, Web of Science, and relevant conference abstracts up to 19 October 2024. The included RCTs examined CDK4/6 inhibitors with ET in HR + HER2− early breast cancer patients. Hazard ratios (HR) with 95% confidence intervals (CI) were calculated to analyze invasive disease-free survival (iDFS).ResultsFour RCTs with 3-year and 4-year iDFS data (n = 17,749) were included. The results showed that the CDK4/6 inhibitor group had significantly better iDFS compared to the ET group at both 3 years (HR = 0.81, 95% CI 0.70–0.94, P = 0.006) and 4 years (HR = 0.78, 95% CI 0.66–0.94, P = 0.007). Subgroup analysis revealed that in LN + patients, the CDK4/6 inhibitor group also had significantly better iDFS at both 3 years (HR = 0.84, 95% CI 0.73–0.97, P = 0.02) and 4 years (HR = 0.74, 95% CI 0.68–0.81, P < 0.00001). For N0 patients, iDFS benefits became more evident over time. At 4 years, combination therapy showed significant improvement (HR = 0.65, 95% CI 0.45–0.94, P = 0.02). For stage II patients, CDK4/6 inhibitors combined with ET showed no statistically significant difference in iDFS at treatment completion (HR = 0.78, 95% CI 0.59–1.05, P = 0.10), but significantly improved iDFS at 4 years (HR = 0.66, 95% CI 0.50–0.87, P = 0.003).ConclusionThe iDFS improvement with CDK4/6 inhibitors becomes more evident over time, suggesting broader benefits and enhanced long-term efficacy for HR+, HER2-breast cancer patients especially with N0 or Stage II.Systematic Review RegistrationPROSPERO database, CRD42024593864.